Brand Personality In “Asmara Gen Z” Cast Endorsements As Glad2glow’s Public Relations Practice On TikTok - Habiba, Latifa Ummu; Lies Utami Efni Safitri (CV Putra Publisher, 2026)
This study aims to analyze the representation of Glad2Glow’s brand personality in the endorsement content of the cast of Asmara Gen Z as a public relations practice on TikTok. The study is motivated by the increasing use of popular culture figures in digital brand communication, particularly in the fast beauty industry, where brands are required to establish identities that are relevant to Generation Z audiences. This study applies Aaker’s brand personality framework, which consists of five dimensions: sincerity, excitement, competence, sophistication, and ruggedness. This research employs a qualitative approach using content analysis methods. Primary data were obtained from 65 TikTok endorsement videos uploaded by eight cast members of Asmara Gen Z promoting Glad2Glow products. Secondary data were collected from journals, books, and relevant literature. Data collection techniques included non-participant observation and documentation, while data analysis was conducted through data reduction, categorization, data presentation, and conclusion drawing. The findings reveal that Glad2Glow’s brand personality is represented through repetitive content patterns integrated with popular TikTok trends. The excitement dimension emerged as the most dominant characteristic, portraying the brand as energetic, trend-aware, and closely connected to Generation Z digital culture. The findings also indicate that the cast endorsements function as a public relations practice through brand humanization, message standardization, and the creation of emotional closeness with audiences. This study confirms that digital endorsement functions not only as a promotional tool but also as a strategic mechanism for brand identity construction on social media.